2004
DOI: 10.1093/jb/mvh134
|View full text |Cite
|
Sign up to set email alerts
|

The ASK1-MAP Kinase Cascades in Mammalian Stress Response

Abstract: The mitogen-activated protein (MAP) kinase cascades play essential roles in a variety of cell processes by influencing transcriptional or translational regulation. ERKs play a central role in survival and mitogenic signaling, while JNKs and p38 MAP kinases are preferentially activated by environmental stresses and are actively involved in various stress responses including cell death, survival and differentiation. Apoptosis signal-regulating kinase 1 (ASK1)--a serine/threonine protein kinase--is a member of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
285
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 312 publications
(289 citation statements)
references
References 42 publications
3
285
0
1
Order By: Relevance
“…ASK1 is known to be one of the key molecules that is involved in oxidative stress-induced cellular apoptosis. 14,21 These findings encouraged us to determine the role of ASK1 and VEGF in oxidative stress-induced endothelial apoptosis. Using cultured endothelial cells from wild-type and ASK1-deficient mice, we found that ASK1 deficiencies significantly attenuated H 2 O 2 -induced endothelial apoptosis, demonstrating the important role of ASK1 in oxidative stress-induced endothelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 is known to be one of the key molecules that is involved in oxidative stress-induced cellular apoptosis. 14,21 These findings encouraged us to determine the role of ASK1 and VEGF in oxidative stress-induced endothelial apoptosis. Using cultured endothelial cells from wild-type and ASK1-deficient mice, we found that ASK1 deficiencies significantly attenuated H 2 O 2 -induced endothelial apoptosis, demonstrating the important role of ASK1 in oxidative stress-induced endothelial apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, ASK1 participates in the JNK and p38 MAPK signaling cascades by phosphorylating MKK4/MKK7 and MKK3/MKK6 respectively . ASK1 is activated in response to various extracellular and intracellular stimuli, such as lipopolysaccharide, ROS, endoplasmic reticulum (ER) stress, and signaling through Fas and TNFa (Matsukawa et al 2004). ASK1 is well known as a proapoptotic, stress-activated signaling molecule, and it is under tight regulation at multiple levels, one of which is negatively regulated by PRDX1 (Kim et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…ASK1 was identified as a MAP kinase kinase kinase involved in the stress-induced apoptosis signaling cascade that activates the SEK1-Jun N-terminal kinase (JNK) and MKK-p38 MAP kinase cascade [16]. ASK1 is activated by death receptor ligands, such as TNF-a and Fas ligand, and by various cytotoxic stresses, such as hydrogen peroxide, anticancer drugs, and growth factor deprivation [17]. Furthermore, endoplasmic reticulum stress and G protein-coupled receptor signaling were recently shown to activate ASK1 [17].…”
Section: Introductionmentioning
confidence: 99%